Levosimendan: a remedy for treating the patients of decompensated heart failure - Dhaliwal, Vikramjit Singh; Gill, Manpreet Singh; ., Monika (International Journal of Advances in Medicine, 2020)
Background: Levosimendan is a new-fangled calcium based sensitizer which is used to treat the patients with congestive or decompensated heart failure. The empirical study reveals that it intensifies myocardial contractility and expands coronary and peripheral vessels without affecting the diastolic function adversely. Levosimendan also performs as an opener of ATP-based K channels in vascular smooth muscle. The empirical research study shows the benefits of usage of levosimendan over other drugs in the treatment of decompensated and congestive heart failure. Methods: Levosimendan has been administered to patients with decompensated heart failure conditions. Infusion of levosimendan started with a dose of 0.1 µg/kg/min and titrated to 0.2 µg/kg/min. The systolic BP has been monitored after the administration of levosimendan to maintain stability in the patient’s BP for the initial 2-3 hours. The suggested duration of infusion of levosimendan in critical heart failure is twenty-four hours. Initially levosimendan is infused in the patients with systolic BP is more than hundred mmHg and diastolic BP is more than sixty mmHg. Results: The outcomes of the usage of Levosimendan have been studied on 80 patients with decompensated heart problems and the comparative study has also been made with other inotropes, respectively. We have also performed a trial on two groups of people named as LIVO and NON-LIVO groups. The research study proves that the usage of levosimendan is better than other inotropes. Levosimendan can be recommended in the standard treatment of patients with acute heart conditions. Conclusions: Levosimendan is offering an effective remedy to treat the patients with decompensated heart failure. In comparison to other inotropes available for the treatment of patients suffering from congestive heart ailments, levosimendan can be considered to be a safe and efficient sensitizer.